Causal relationship between air pollution and infections: a two-sample Mendelian randomization study - Yang, Shengyi; Tong, Tong; Wang, Hong; Li, Zhenwei; Wang, Mengmeng; Ni, Kaiwen (Frontiers in Public Health, 2024)
Background: Traditional observational studies exploring the association between air pollution and infections have been limited by small sample sizes and potential confounding factors. To address these limitations, we applied Mendelian randomization (MR) to investigate the potential causal relationships between particulate matter (PM2.5, PM2.5-10, PM10), nitrogen dioxide, and nitrogen oxide and the risks of infections.Methods: Single nucleotide polymorphisms (SNPs) related to air pollution were selected from the genome-wide association study (GWAS) of the UK Biobank. Publicly available summary data for infections were obtained from the FinnGen Biobank and the COVID-19 Host Genetics Initiative. The inverse variance weighted (IVW) metaanalysis was used as the primary method for obtaining the Mendelian randomization (MR) estimates. Complementary analyses were performed using the weighted median method, MR-Egger method, and MR Pleiotropy Residual Sum and Outlier (MR-PRESSO) test.The fixed-effect IVW estimate showed that PM2.5, PM2.5-10 and Nitrogen oxides were suggestively associated with COVID-19 [For PM2.5: IVW (fe): OR 3.573(1.218,5.288), PIVW(fe)=0.021; For PM2.5-10: IVW (fe): OR 2.940(1.385,6.239), PIVW(fe)=0.005; For Nitrogen oxides, IVW (fe): OR 1.898(1.318,2.472), PIVW(fe)=0.010]. PM2.5, PM2.5-10, PM10 and Nitrogen oxides were suggestively associated with bacterial pneumonia [For PM2.5: IVW(fe): OR 1.720(1.007,2.937), PIVW(fe)=0.047; For PM2.5-10: IVW(fe): OR 1.752(1.111,2.767), P IVW(fe)=0.016; For PM10: IVW(fe): OR 2.097(1.045,4.208), PIVW(fe)=0.037; For Nitrogen oxides, IVW(fe): OR 3.907(1.209,5.987), PIVW(fe)=0.023]. Furthermore, Nitrogen dioxide was suggestively associated with the risk of acute upper respiratory infections, while all air pollution were not associated with intestinal infections. Conclusions: Our results support a role of related air pollution in the Corona Virus Disease 2019, bacterial pneumonia and acute upper respiratory infections. More work is need for policy formulation to reduce the air pollution and the emission of toxic and of harmful gas.